The behaviour of shear walls in global skeletal frames [microfilm] - Kong, Chak Hing (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2005